2017
DOI: 10.1111/vco.12361
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic reovirus therapy: Pilot study in dogs with spontaneously occurring tumours

Abstract: Oncolytic virotherapy is a novel treatment involving replication-competent virus in the elimination of cancer. We have previously reported the oncolytic effects of reovirus in various canine cancer cell lines. This study aims to establish the safety profile of reovirus in dogs with spontaneously occurring tumours and to determine a recommended dosing regimen. Nineteen dogs with various tumours, mostly of advanced stages, were treated with reovirus, ranging from 1.0 × 10 to 5.0 × 10 TCID given as intratumour in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…Oncolytic virotherapy has been recognized as a promising option for human cancer treatment particularly benefiting from the recent advances in molecular virology and oncology . However, application of oncolytic virotherapy within the field of veterinary medicine remains limited . Our studies have focused on the oncolytic feasibility and mechanism of oncolytic activity of CDV within CMTAC CIPp cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oncolytic virotherapy has been recognized as a promising option for human cancer treatment particularly benefiting from the recent advances in molecular virology and oncology . However, application of oncolytic virotherapy within the field of veterinary medicine remains limited . Our studies have focused on the oncolytic feasibility and mechanism of oncolytic activity of CDV within CMTAC CIPp cells.…”
Section: Discussionmentioning
confidence: 99%
“…In human cancers, promising results have been obtained in clinical trials using oncolytic virotherapy . In the veterinary field, several viruses of different virus families including Adeno ‐, Pox ‐, Reo ‐, and Paramyxoviridae , have been reported as oncolytic agents before or after genetic engineering and exhibit anti‐tumour activities …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oncolytic virotherapy is a novel treatment strategy for the treatment of canine and feline cancers, as well as those of humans . While many kinds of viruses have been proposed as candidates for virotherapy, our laboratory has been researching the use of a naturally occurring reovirus, the serotype‐3 Dearing strain, as a new approach for treating canine cancer in veterinary medicine . Reovirus is a ubiquitous and non‐enveloped mammalian virus with a genome that consists of 10 segments of double‐stranded RNA.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, those studies showed that there was no relationship between Ras activation and susceptibility to reoviral killing in canine cancers. To assess the efficacy of reovirus in a clinical setting, we conducted a pilot study of reovirus therapy in tumour‐bearing dogs . However, the pilot study did not include dogs with histiocytic sarcoma.…”
Section: Introductionmentioning
confidence: 99%